Assessment of the Effects of Pregnancy-Induced Hypertension upon Pregnant Women and Their Pregnancy Outcome in Erbil City
Objective: A descriptive analytical study was conducted on pregnant women who have pregnancy-induced hyperteusion ¢IH) and were delivered in Maternity Hospital at Erbil City, in order to identify the effects of PIH upon pregnant women and their pregnancy outcome. Methods: A purposive sample of one hundred pregnant women who had PIH, as study group and one hundred normal pregnant women, as control group was selected from the emergency, obstetric wal.ds and delivery room of Maternity Hospital in Erbil City. The data were collected by using a questiomaire format through interviewing and reviewing the records of both groups (study and control group). Pesults: The study result shows that the effects of PIH upon pregnancy outcome were include: (20.2 distress, (13.4 %) Premafurfty, (9.6 %) Respiratory disa.ess. §y;dron;e, (8.7 %) olig-a-a